A study of mechanical properties of foil materials for the GEM detector proposed for the CMS muon system upgrade at LHC. Issue 9 (15th November 2017) - Saviano, G.; Muhammad, S.; Bianco, S.; Benussi, L.; Piccolo, D.; Caponero, M.A.; Passamonti, L.; Pierluigi, D.; Russo, A.; Lalli, A.; Valente, M.; Sarasini, F.; et al.
Abstract : The material characterization of the gaseous electron multiplier (GEM) detectors is presented in this article; mechanical tests were performed to examine the mechanical performance of polyimide (Kapton) and GEM foil. Bearing in mind the mechanical stresses imposed during the assembly and subsequently during operation at Compact Muon Solenoid (CMS). The detectors will run for many years in the harsh radiation and environmental conditions at the CMS. In view of this a series of the tensile tests were performed by using different samples which were prepared accordingly, i.e. a set of the samples was exposed to neutron and another exposed to gamma radiation, and then these were made dry and wet to assess the effects of radiation and humidity on their tensile properties. In this paper the experimental setup, testing procedures, sampling and detailed results are presented. In general, due to the radiation and environment variation conditions the degradation of the GEM material is not significant with respect to its toughness, but the Young's modulus was effected. POLYM. ENG. SCI., 58:1539–1547, 2018. © 2017 Society of Plastics Engineers